Internal conflicts in Myanmar : transnational consequences - Raghavan, V. R.; Centre for Security Analysis (Madras, India); Institute of Southeast Asian Studies (New Delhi : Vij Books India, 2011)
Papers presented at a seminar organized in collaboration with Institute of South East Asian Studies, Singapore, in May 2010.
'Published for Centre for Security Analysis, Chennai, India.'
Includes bibliographical references.
Keywords: Ethnic conflict -- Burma; Burma -- Ethnic relations; Burma -- Foreign relations